IFPRI Malawi Monthly Maize Market Report, June 2025 - Benson, Anderson (International Food Policy Research Institute, 2025)
Highlights Retail prices of maize increased by 8 percent in June. Prices rose in all regions of Malawi despite continued imports. Maize retailed above the government-mandated price in 13 out of 26 monitored markets.